Photolytic changes in the morphology of porphyrin-phthalocyanine nanostructures (P-PcNs) in the presence of platinum and gold salts - George, R. C.; Sarah, D'Souza; Durmuş, Mahmut; Tebello, Nyokong (Taylor & Francis Inc, 2017)
Porphyrin-phthalocyanine nanostructures (P-PcNs) have been fabricated by electrostatic self-assembly of two oppositely charged molecules. The negatively charged molecule, meso-tetra-(4-phenylsulphonate) porphyrin (HT) and the positively charged species; {1,(4)-tetrakis-[(N-methyl(3-pyridyloxy)phthlocyaninato] chloro gallium(III)} sulphate, {2,(3)-tetrakis-[(N-methyl{(2-mercaptopyridine) phthalocyaninato} hydroxy manganese(III)} sulphate, {1,(4)-tetrakis-[(N-methyl-(3-pyridyloxy) phthalocyaninato] chloro indium(III)} sulphate, {2,3-octakis-{[(N-methyl-2-mercaptopyridine) phthalocyaninato] acetato manganese(III)} sulphate, {2,(3)-tetrakis-[(N-methyl(3-pyridyloxy) phthlocyaninato] choro gallium(III)} sulphate, {2,3-octakis[(N-methy-3-pyridyloxy) phthalocyaninato] chloro indium(III)} sulphate, and {2,(3)-tetrakis-[(N-methyl (3-pyridyloxy) phthalocyaninato] chloro indium(III)} sulphate. Transmission electron microscopic (TEM) images showed that the formed nanostructures ranged from nanosheets to nanorods and nanotubes. The UV-Vis spectra confirmed that the molecules formed J-aggregates. The P-PcNs were exposed to incandescence light in the presence of platinum and gold salts. It was observed that the presence of platinum salts resulted in the destruction of the P-PcNs with possible formation of a Pt-Pc complex. While with the gold salt, the structures of P-PcNs were not only retained but were also enhanced to longer nanorods and nanofibers with the formation of gold nanoparticles.
Keywords: Porphyrin; phthalocyanines; nanorods; nanostructures; photolysis; J-aggregation